2016
DOI: 10.1177/1535370216644530
|View full text |Cite|
|
Sign up to set email alerts
|

Benzopyrene promotes lung cancer A549 cell migration and invasion through up-regulating cytokine IL8 and chemokines CCL2 and CCL3 expression

Abstract: Tobacco-sourced carcinogen including benzopyrene (B[a]P) in lung cancer metastasis has not been fully reported. In this study, lung carcinoma A549 cell line was used to investigate the potential roles of tobacco-sourced B[a]P on cell metastasis and invasion and to assess its underlying mechanism. Effects of tobacco-sourced carcinogen on A549 cell proliferation, metastasis, and invasion were analyzed using MTT assay, Transwell assay, and scratch method, respectively. The effects of tobacco-sourced carcinogen on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…CCL2 could recruit monocytes, memory T cells, and dendritic cells to the sites of inflammation produced either by tissue injury or infection, as well as the tumor microenvironment . CCL2 is produced by a variety of tumors and plays an important role in cancer progression, particularly in promoting cancer cell migration and invasion . Our study showed that CCL2 was highly expressed in the LUAD microenvironment; however, the reason for this is unclear.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…CCL2 could recruit monocytes, memory T cells, and dendritic cells to the sites of inflammation produced either by tissue injury or infection, as well as the tumor microenvironment . CCL2 is produced by a variety of tumors and plays an important role in cancer progression, particularly in promoting cancer cell migration and invasion . Our study showed that CCL2 was highly expressed in the LUAD microenvironment; however, the reason for this is unclear.…”
Section: Discussionmentioning
confidence: 67%
“…23 CCL2 is produced by a variety of tumors and plays an important role in cancer progression, particularly in promoting cancer cell migration and invasion. 24 Our study showed that CCL2 was highly expressed in the LUAD microenvironment; however, the reason for this is unclear. In Lewis lung carcinoma, TNFα released by tumor cell-activated macrophages is critical for increased CCL2 production by tumor cells.…”
Section: Discussionmentioning
confidence: 68%
“…Benzopyrene exposure is associated with pregnancy loss, alterations in fetal development (Zhang et al 2016), alterations in weights of the reproductive organs, damage in ovarian follicles, and infertility and abnormal fetal development in laboratory animal models (Borman et al 2000;Csaba et al 1993; MacKenzie and Angevine 1981; Rigdon and Rennels 1964). Analysis of epigenetic effects of benzopyrene was studied in four breast cancer cell lines (MCF-7, T47-D, MDA MB 231, and HCC-1806) by Sadikovic and Rodenhiser (2006).…”
Section: Epigenetic Effectsmentioning
confidence: 99%
“…57 Recently, some studies provided mechanistic clues showing that BaP may contribute to lung cancer cell invasion and metastasis by upregulating proinflammatory chemokines (IL8, CCL-2, CCL-3) and the one of the master regulator of the epithelial-to-mesenchymal transition, Twist. 58,59 Moreover, BaP was able to induce cell migration in triple-negative breast cancer MDA-MB-231 cells through a lipoxygenase-and Src-dependent pathway, notably by increasing the secretion of metalloproteinase MMP-2 and MMP-9. 60 BaP treatment was also able to increase the metastatic potential of hepatocellular carcinoma cell lines in a mouse model, likely through an activation of both angiogenesis and NF-kB pathway.…”
Section: Hallmark 6: Activating Invasion and Metastasismentioning
confidence: 99%